A posteriori error estimation techniques for finite element methods - Verfürth, Rüdiger (Numerical mathematics and scientific computation., 2013)
A posteriori error estimation techniques are fundamental to the efficient numerical solution of PDEs arising in physical and technical applications. This text gives a unified approach to these techniques and guides graduate students, researchers, and practitioners towards understanding, applying and developing self-adaptive discretization methods.